Jurisprudential Inquiry sebagai Model Pembelajaran Alternatif untuk Mata Pelajaran Pendidikan Kewarganegaraan Di Sekolah Menengah Atas - Japar, Muhammad (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2017)
This study explores the learning model of civic education for Senior High School students.The purpose of Civic education in Senior High School are preparing to be smart and good citizen. In fact,learning program by teacher isn’t enough to make student active. To make student active in civic eduction learning, the idea is application Jurisprudential Inquiryas a model.This qualitative case study draws on interview from eight students and a teacher in Senior High School. The research shows that Jurisprudential inquiry model can be used as an alternative model for civic education as it is effective, efficient and attractive.